Black tea bioactive phytoconstituents realign NRF2 for anticancer activity in lung adenocarcinoma - Datta, Suchisnigdha; Bishayee, Anupam; Sinha, Dona (Frontiers in Pharmacology, 2023)
Constitutive activation of nuclear factor erythroid 2-related factor 2 (NRF2) is pivotal in bestowing therapy resistance in cancer cells. Several phytochemicals have been reported with the potential of modulating NRF2. Therefore, it was hypothesized that NRF2-deregulated chemoresistance in lung adenocarcinoma (LUAD) may be counteracted by theaflavin-rich black tea (BT). A non-responsive LUAD cell line, A549, was best sensitized towards cisplatin upon pre-treatment with BT. BT-mediated NRF2 reorientation was observed to be dependent on concentration and duration of treatment as well as on the mutational profile of NRF2 in A549 cells. Transient exposure of low-concentration BT hormetically downregulated NRF2, its downstream antioxidants, and drug transporter. BT also influenced the Kelch-like ECH-associated protein (KEAP1)-dependent cullin 3 (Cul3) and -independent epidermal growth factor receptor (EGFR)/rat sarcoma virus (RAS)/rapidly accelerated fibrosarcoma (RAF)/extracellular signal-regulated kinase 1/2 (ERK)/matrix metalloproteinase (MMP)-2 and MMP-9. The realignment of NRF2 in KEAP1-suppressed A549 cells enhanced the chemotherapeutic outcome. But a higher concentration of the same BT surprisingly upregulated NRF2 and its transcriptional targets with a subsequent decrease in the NRF2-regulatory machinery in NCI-H23 cells (a KEAP1-overexpressed LUAD cell-line), ultimately resulting in a better anticancer response. The BT-mediated bidirectional NRF2 modulation was reconfirmed upon comparison with the action of a pharmacological NRF2 inhibitor, ML-385, in A549 and a known NRF2 activator, tert-butylhydroquinone, in NCI-H23 respectively. BT-mediated regulation of NRF2-KEAP1 and their upstream networks (EGFR/RAS/RAF/ERK) sufficed as a better anticancer agent than synthetic NRF2 modulators. Therefore, BT may be indicated as a potent multi-modal small molecule for increasing drug responsiveness in LUAD cells by maintaining NRF2/KEAP1 axis at an optimum level.